2013
DOI: 10.5402/2013/178646
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Pressure of Ciprofloxacin and Gentamicin on Biofilm Development by an Endoscope-Isolated Pseudomonas aeruginosa

Abstract: This work aims at characterizing endoscope biofilm-isolated (PAI) and reference strain P. aeruginosa (PA) adhesion, biofilm formation and sensitivity to antibiotics. The recovery ability of the biofilm-growing bacteria subjected to intermittent antibiotic pressure (ciprofloxacin (CIP) and gentamicin (GM)), as well as the development of resistance towards antibiotics and benzalkonium chloride (BC), were also determined. The capacity of both strains to develop biofilms was greatly impaired in the presence of CIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…It is one of the main causes of hospital-acquired infections (Machado et al, 2013). Effective antibiotics are limited because infections by P. aeruginosa are hard to defy, as it is virulent, acquires antibiotic resistance and resists disinfectants (Higgins et al, 2001;Zavascki et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the main causes of hospital-acquired infections (Machado et al, 2013). Effective antibiotics are limited because infections by P. aeruginosa are hard to defy, as it is virulent, acquires antibiotic resistance and resists disinfectants (Higgins et al, 2001;Zavascki et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm resistance mechanisms include not only the reaction-diffusion limitation of antimicrobial access to the biofilm-entrapped bacteria (Gilbert et al, 2003), but also the expression of spatially heterogeneous, less susceptible phenotypes, caused either by growth as a biofilm per se, or through the expression of high cell density, or starvation phenotypes. The use of certain active substances in biocides in various settings may contribute to the increased occurrence of antibiotic resistant bacteria (Machado et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that most of the antibacterial agents are unable to penetrate in biofilm consortia, that leads to serious therapeutic problems in control of various infections [3,4]. Biofilms act a reservoir of J Microbiol Infect Dis www.jmidonline.org Vol 10, No 1, March 2020 pathogenic bacteria that can detach, resume their planktonic state, and contaminate new surfaces and patients [5]. P. aeruginosa is one of the leading colonizers in clinical setups including indwelling biomedical catheters and implants [1].…”
mentioning
confidence: 99%
“…P. aeruginosa is one of the leading colonizers in clinical setups including indwelling biomedical catheters and implants [1]. Most of the times these pathogens adopt a biofilm mode of life to nullify the toxic effect of antibiotics [3][4][5]. According to research reports, biofilm communities of P. aeruginosa consist of heterogeneous population, e.g.…”
mentioning
confidence: 99%
“…aeruginosa is an opportunistic pathogen and responsible for hospital-acquired infections (1,2). P. areuginosa is a virulent, antibiotic resistant and sometime resists disinfectants.…”
Section: Introductionmentioning
confidence: 99%